I love you... and heroin: care and collusion among drug-using couples. - Simmons, Janie; Singer, Merrill (Substance abuse treatment, prevention, and policy, 2006)
Romantic partnerships between drug-using couples, when they are recognized at all, tend to be viewed as dysfunctional, unstable, utilitarian, and often violent. This study presents a more nuanced portrayal by describing the interpersonal dynamics of 10 heroin and cocaine-using couples from Hartford, Connecticut.
Keywords: Adult; Cocaine-Related Disorders; Connecticut; Drug Users; Family Characteristics; Female; Health Behavior; Heroin Dependence; Humans; Interpersonal Relations; Interviews as Topic; Love; Male; Middle Aged; Social Behavior